A Photo-Induced Spin Crossover Based Molecular Switch and Spin Filter Operating at Room Temperature - Cardenas-Jiron, G; Borges-Martinez, M; Montenegro-Pohlhammer, N (Royal Society of Chemistry, 2021)
Since Venkataramani et al. (Science, 2011, 331(6016), 445-448) reported reversible, room-temperature light-induced spin crossover in Ni-porphyrin functionalized with a phenylazopyridine ligand (NiTPP-PAPy), this complex has attracted the attention of many researchers due to its potential applications in molecular-based devices. In this work, we perform a detailed study, by means of DFT and WFT methodologies, focused on the deposition of NiTP-PAPy over an Au(111) surface, followed by DFT-NEGF calculations employing a gold surface and the tip of an STM as electrodes, in order to probe the deposited complex s transport properties. Our DFT calculations show that not only the metalled porphyrin is strongly adsorbed on the surface, in both the high (HS) and low spin (LS) configurations, but also, and more importantly, photoinduced switching is preserved upon adsorption, a fact that is also confirmed through WFT and TD-DFT calculations. Moreover, our DFT-NEGF calculations indicate that the current passing through the molecular junction-like systems is much higher in the HS configuration than in the LS one, along with the fact that the current calculated in the ferromagnetic junction is highly spin-polarized. These remarkable transport properties suggest that the complex could be used as a component in molecular switches based on the total current passing through the system, modulated by light irradiation, spin filters due to the spin polarization of the carriers in the HS configuration, or even in two-step rectifiers combining the two features mentioned above, all of these operating at room temperature, giving to this complex the potential to be an active element in all kinds of future spintronic devices. © 2021 The Royal Society of Chemistry.